Eksperimen Pembelajaran Matematika Dengan Strategi Discovery Learning Dan Project Based Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa Kelas VII SMP Negeri 2 Sawit Tahun 2016/2017 - Octavina, Ayunda, Dra. Sri Sutarni, M.Pd (2017)
There are three aims of the research: (1) examine the effect learning strategy (discovery learning and project based learning) toward mathematics learning achievement, (2) examine the effect of learning motivation toward mathematics learning achievement, (3) examine the interaction between learning strategy and learning motivation toward mathematics learning achievement. The type of research was a quantitative research with quasi experimental design. The sampling technique used cluster random sampling. The population of the research was all students of VII Grade of SMP Negeri 2 Sawit yaer 2016/2017. The research sample consisted of two classes. Methode of data collection use the test, questionnaires, and documentation. Data were analyzed use analysis of variance with two different cell lines that ware previously done using methode Lilliefors normality test and homogenity test using Bartlett method. The findings of the research with α=5% (1) there was effect of learning toward mathematics learning achievement, (2) there was effect of learning motivation toward mathematics learning achievement, (3) there was no interaction between learning strategy and learning motivation toward mathematics learning achievement. Keyword: discovery, project, learning achievement, motivation